Policing Protest Events: The Great Strike of 1877 and WTO Protests of 1999 - DeMichele, Matthew (American journal of criminal justice, 2008)
The notion of the police as protecting dominant economic interests is explored by presenting two case studies of direct action social movements occurring nearly 100 years apart. Recent protests in response to a non-state international organization (the World Trade Organization) are compared with a major labor strike of the late 19th century (the Great Strike of 1877). Historical data supports the contention that, despite many changes to contemporary policing strategies, the police are routinely used to protect existing economic structures. These narratives demonstrate how shifts in economic institutions shape formal social control practices. Comparing these events reveals how new technologies have allowed for certain adaptations and innovations for contemporary protesting and protest breaking activities. It is argued that the police institution should not be understood as only charged with responding reactively to criminal violations, but rather as serving more important social functions such as protecting dominant economic structures.